To defend this sunrise : Black women's activism and the authoritarian turn in Nicaragua - Morris, Courtney Desiree (Rutgers University Press, 2023)
"To Defend this Sunrise examines how black women on the Caribbean coast of Nicaragua engage in regional, national, and transnational modes of activism to remap the nation's racial order under conditions of increasing economic precarity and autocracy. The book considers how, since the 19th century, black women activists have resisted historical and contemporary patterns of racialized state violence, economic exclusion, territorial dispossession, and political repression. Specifically, it explores how the new Sandinista state under Daniel Ortega and Rosario Murillo has utilized multicultural rhetoric as a mode of political, economic, and territorial dispossession. In the face of the Sandinista state's co-optation of multicultural discourse and growing authoritarianism, black communities have had to recalibrate their activist strategies and modes of critique to resist these new forms of "multicultural dispossession." This concept describes the ways that state actors and institutions drain multiculturalism of its radical, transformative potential by espousing the rhetoric of democratic recognition while simultaneously supporting illiberal practices and policies that undermine black political demands and weaken the legal frameworks that provide the basis for the claims of these activists against the state"-- Provided by publisher.
Description based upon print version of record.
Keywords: Women, Black -- Political activity -- Nicaragua -- Bluefields.; Civil rights -- Nicaragua.; Multiculturalism -- Nicaragua.; Black people -- Nicaragua -- Politics and government.; Indigenous peoples -- Nicaragua -- Politics and government.; Nicaragua -- Politics and government -- 1990-; Autochtones -- Nicaragua -- Politique et gouvernement.; Multiculturalisme -- Nicaragua.; Femmes noires -- Activité politique -- Nicaragua -- Bluefields.; Personnes noires -- Nicaragua -- Politique et gouvernement.; Nicaragua -- Politique et gouvernement -- 1990-1996.; SOCIAL SCIENCE / General.; Black people -- Politics and government; Civil rights; Indigenous peoples -- Politics and government; Multiculturalism; Politics and government; Women, Black -- Political activity; Nicaragua; Nicaragua -- Bluefields; Since 1990